2021
DOI: 10.15392/bjrs.v9i3.1734
|View full text |Cite
|
Sign up to set email alerts
|

Influence of image reconstruction protocols on the image quality of a small animal PET scanner using 18F and 11C

Abstract: The small animal positron emission tomography (PET) scanner from Molecular Imaging Laboratory (LIM/CDTN) is dedicated to pre-clinical studies on new 18F and 11C-based radiopharmaceuticals and to development of novel applications for well-known radiopharmaceuticals. Thus, quality control tests recommended by the publication NEMA NU 4-2008 are routinely carried out to ensure the proper performance of PET scanner. The aim of this work was to evaluate the influence of image reconstruction protocols on the image qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This study allowed evaluate the influence of standard resolution and high resolution modes in quantification of SUV_mean and SUV_max to LabPET SOLO 4 scanner of LIM/CDTN. As observed in previous work with IQ phantom [3], the use of high resolution mode, despite promoting a slight improvement in the definition of structures in the qualitative analysis (visual inspection), did not significantly change the quantification of radiopharmaceutical uptake in the analyzed tissues.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This study allowed evaluate the influence of standard resolution and high resolution modes in quantification of SUV_mean and SUV_max to LabPET SOLO 4 scanner of LIM/CDTN. As observed in previous work with IQ phantom [3], the use of high resolution mode, despite promoting a slight improvement in the definition of structures in the qualitative analysis (visual inspection), did not significantly change the quantification of radiopharmaceutical uptake in the analyzed tissues.…”
Section: Discussionsupporting
confidence: 65%
“…This protocol is presented in Table 1. It was observed that the use of the standard resolution mode did not show significant differences when compared to high resolution mode [3]. In the preset study, our objective is to verify if this finding also applies (or not) to PET images of small animals, which have more complex internal structures than those of the IQ phantom.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation